Simulações de parâmetros genéticos a partir de microssatélites: contribuições para a conservação de recursos florestais de biomas brasileiros - Serrote, Caetano Miguel Lemos (2022)
The increasing destruction of forest ecosystems has been of concern to society worldwide and demands for more effective conservation strategies for these genetic resources. In this research, microsatellite markers data were used in computer simulations aiming the conservation of forest resources in the Brazilian biomes. The EasyPop program was used to perform simulations in forest populations representing the different Brazilian biomes in order to generate genetic, ecological and reproductive parameters useful for planning interventions for conservation of these resources. The results indicate a trend for low genetic variability in the studied populations as a consequence of anthropic activities. In this context, our work reinforces the need for adopting measures aiming to minimize the loss of genetic diversity, such as promoting gene flow between forest populations/fragments.